Podatek dochodowy a procesy decyzyjne w przedsiębiorstwie (ze szczególnym uwzględnieniem kształtowania kosztów amortyzacji środków trwałych) - Kurková, Karina (Income Tax Versus Decision in the Enterprise (with Taking the Forming of Capital Assets Depreciation Costs into Consideration), 2005)
This article indicates the conditions accompanying decisions being made by the managers of the enterprise as well as the place of the tax policy in decision processes of the trade units. Special attention was placed on the income tax. Tax policy connected with the income tax offers a lot of possibilities to choose from while making trade decisions. In order to demonstrate the opportunities of choice resulting from the construction of the income tax, the variants of shaping costs of depreciation of fixed assets have been discussed. Depreciation as the cost affecting the taxation base creates a wide range of possibilities of its decrease or increase in order to achieve the main objectives of not only the tax policy but also enterprise policy as a whole.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 96-103